Technologies for Biological and Bioelectrochemical Removal of Inorganic Nitrogen from Wastewater: A Review - Diplina Paul; Abhisek Banerjee (Nitrogen, 2022)
Water contamination due to various nitrogenous pollutants generated from wastewater treatment plants is a crucial and ubiquitous environmental problem now-a-days. Nitrogen contaminated water has manifold detrimental effects on human health as well as aquatic life. Consequently, various biological treatment processes are employed to transform the undesirable forms of nitrogen in wastewater to safer ones for subsequent discharge. In this review, an overview of various conventional biological treatment processes (viz. nitrification, denitrification, and anammox) have been presented along with recent novel bioelectrochemical methods (viz. microbial fuel cells and microbial electrolysis cells). Additionally, nitrogen is an indispensable nutrient necessary to produce artificial fertilizers by fixing dinitrogen gas from the atmosphere. Thus, this study also explored the potential capability of various nitrogen recovery processes from wastewater (like microalgae, cyanobacteria, struvite precipitation, stripping, and zeolites) that are used in industries. Further, the trade-offs, challenges posed by these processes have been dwelt on along with other biological processes like CANON, SHARON, OLAND, and others.